2017
DOI: 10.3390/met7040117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of In-Situ Cu–TiH2–C and Cu–Ti–C Nanocomposites Produced by Mechanical Milling and Spark Plasma Sintering

Abstract: This study focuses on the fabrication and microstructural investigation of Cu-TiH2-C and Cu-Ti-C nanocomposites with different volume fractions (10% and 20%) of TiC. Two mixtures of powders were ball milled for 10 h, consequently consolidated by spark plasma sintering (SPS) at 900 and 1000 • C producing bulk materials with relative densities of 95-97%. The evolution process of TiC formation during sintering process was studied by using X-ray diffraction (XRD), scanning electron microscopy (SEM), and high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Therefore, it is reasonable to presume that the first shrinkage in the DIL curves is caused by the decomposition of TiH 2 , producing hydrogen and reducing the oxide in the Cu particles subsequently. This claim has been confirmed by the research conducted by Oanh et al [36] which showed that oxygen in the in-situ formed Cu-TiC composite can be reduced by the addition of a small amount of TiH 2 .…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, it is reasonable to presume that the first shrinkage in the DIL curves is caused by the decomposition of TiH 2 , producing hydrogen and reducing the oxide in the Cu particles subsequently. This claim has been confirmed by the research conducted by Oanh et al [36] which showed that oxygen in the in-situ formed Cu-TiC composite can be reduced by the addition of a small amount of TiH 2 .…”
Section: Discussionsupporting
confidence: 60%
“…For copper matrix composites, one of the promising reinforcements is titanium carbide, TiC, which is the most thermodynamically stable compound in the Ti–C–Cu system. TiC–Cu composites have recently been obtained through different processing routes [3,4,5,6,7,8,9,10,11,12]. The synthesis of carbide-containing composite materials from different sources of carbon has attracted attention due to the possibility of controlling the size of the carbide particles and their distribution in the matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials containing ceramic compounds can be manufactured via exsitu [1,2] or in-situ routes [3][4][5]. The ex-situ route is based on adding a previously synthesized compound to the matrix.…”
Section: Introductionmentioning
confidence: 99%